Clinical Practice Guideline (Update): Earwax (Cerumen Impaction). (3rd January 2017) - Schwartz, Seth R.; Magit, Anthony E.; Rosenfeld, Richard M.; Ballachanda, Bopanna B.; Hackell, Jesse M.; Krouse, Helene J.; Lawlor, Claire M.; Lin, Kenneth; Parham, Kourosh; Stutz, David R.; Walsh, Sandy; Woodson, Erika A.; et al.
Abstract : Objective: This update of the 2008 American Academy of Otolaryngology—Head and Neck Surgery Foundation cerumen impaction clinical practice guideline provides evidence‐based recommendations on managing cerumen impaction. Cerumen impaction is defined as an accumulation of cerumen that causes symptoms, prevents assessment of the ear, or both. Changes from the prior guideline include a consumer added to the development group; new evidence (3 guidelines, 5 systematic reviews, and 6 randomized controlled trials); enhanced information on patient education and counseling; a new algorithm to clarify action statement relationships; expanded action statement profiles to explicitly state quality improvement opportunities, confidence in the evidence, intentional vagueness, and differences of opinion; an enhanced external review process to include public comment and journal peer review; and 3 new key action statements on managing cerumen impaction that focus on primary prevention, contraindicated intervention, and referral and coordination of care. Purpose: The primary purpose of this guideline is to help clinicians identify patients with cerumen impaction who may benefit from intervention and to promote evidence‐based management. Another purpose of the guideline is to highlight needs and management options in special populations or in patients who have modifying factors. The guideline is intended for all clinicians who are likely to diagnose and manage patients with cerumen impaction, and it applies to any setting in which cerumen impaction would be identified, monitored, or managed. The guideline does not apply to patients with cerumen impaction associated with the following conditions: dermatologic diseases of the ear canal; recurrent otitis externa; keratosis obturans; prior radiation therapy affecting the ear; previous tympanoplasty/myringoplasty, canal wall down mastoidectomy, or other surgery affecting the ear canal. Key Action Statements: The panel made a strong recommendation that clinicians should treat, or refer to a clinician who can treat, cerumen impaction, defined as an accumulation of cerumen that is associated with symptoms, prevents needed assessment of the ear, or both. The panel made the following recommendations : (1) Clinicians should explain proper ear hygiene to prevent cerumen impaction when patients have an accumulation of cerumen. (2) Clinicians should diagnose cerumen impaction when an accumulation of cerumen, as seen on otoscopy, is associated with symptoms, prevents needed assessment of the ear, or both. (3) Clinicians should assess the patient with cerumen impaction by history and/or physical examination for factors that modify management, such as ≥1 of the following: anticoagulant therapy, immunocompromised state, diabetes mellitus, prior radiation therapy to the head and neck, ear canal stenosis, exostoses, and nonintact tympanic membrane. (4) Clinicians should not routinely treat cerumen in patients who are asymptomatic and whose ears can be adequately examined. (5) Clinicians should identify patients with obstructing cerumen in the ear canal who may not be able to express symptoms (young children and cognitively impaired children and adults), and they should promptly evaluate the need for intervention. (6) Clinicians should perform otoscopy to detect the presence of cerumen in patients with hearing aids during a health care encounter. (7) Clinicians should treat, or refer to a clinician who can treat, the patient with cerumen impaction with an appropriate intervention, which may include ≥1 of the following: cerumenolytic agents, irrigation, or manual removal requiring instrumentation. (8) Clinicians should recommend against ear candling for treating or preventing cerumen impaction. (9) Clinicians should assess patients at the conclusion of in‐office treatment of cerumen impaction and document the resolution of impaction. If the impaction is not resolved, the clinician should use additional treatment. If full or partial symptoms persist despite resolution of impaction, the clinician should evaluate the patient for alternative diagnoses. (10) Finally, if initial management is unsuccessful, clinicians should refer patients with persistent cerumen impaction to clinicians who have specialized equipment and training to clean and evaluate ear canals and tympanic membranes. The panel offered the following as options : (1) Clinicians may use cerumenolytic agents (including water or saline solution) in the management of cerumen impaction. (2) Clinicians may use irrigation in the management of cerumen impaction. (3) Clinicians may use manual removal requiring instrumentation in the management of cerumen impaction. (4) Last, clinicians may educate/counsel patients with cerumen impaction or excessive cerumen regarding control measures.